2023
DOI: 10.3390/ijms24087118
|View full text |Cite
|
Sign up to set email alerts
|

Severe Trauma-Induced Coagulopathy: Molecular Mechanisms Underlying Critical Illness

Abstract: Trauma remains one of the leading causes of death in adults despite the implementation of preventive measures and innovations in trauma systems. The etiology of coagulopathy in trauma patients is multifactorial and related to the kind of injury and nature of resuscitation. Trauma-induced coagulopathy (TIC) is a biochemical response involving dysregulated coagulation, altered fibrinolysis, systemic endothelial dysfunction, platelet dysfunction, and inflammatory responses due to trauma. The aim of this review is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…presenting with acute respiratory failure, the interstitial syndrome identified by LUS could be difficult to be attributed to COVID-19 pneumonia rather than to a decompensated previous illness [80]. A recently published systematic review including 66 articles with a pool of 4687 patients observed that the most frequent ultrasound findings in COVID-19 patients were B-lines and pleural abnormalities and confirmed the association between a high LUS score at admission and unfavourable outcomes [84][85][86]. In a retrospective study including 93 patients with a suspected COVID-19 infection admitted to the ED, LUS was found to have sensitivity and negative predictive value (93.3% and 94.1%, respectively) similar to a CT but, instead, a much lower specificity, positive predictive value, and accuracy (21.3%, 19.2%, and 33.3%, respectively) [87].…”
Section: Does My Patient Have Covid-19?mentioning
confidence: 89%
“…presenting with acute respiratory failure, the interstitial syndrome identified by LUS could be difficult to be attributed to COVID-19 pneumonia rather than to a decompensated previous illness [80]. A recently published systematic review including 66 articles with a pool of 4687 patients observed that the most frequent ultrasound findings in COVID-19 patients were B-lines and pleural abnormalities and confirmed the association between a high LUS score at admission and unfavourable outcomes [84][85][86]. In a retrospective study including 93 patients with a suspected COVID-19 infection admitted to the ED, LUS was found to have sensitivity and negative predictive value (93.3% and 94.1%, respectively) similar to a CT but, instead, a much lower specificity, positive predictive value, and accuracy (21.3%, 19.2%, and 33.3%, respectively) [87].…”
Section: Does My Patient Have Covid-19?mentioning
confidence: 89%
“…Conversely, in the group Citrate, the blood flow rate was low to minimize the load of citrate, and this soft dialysis could play a role in ensuring the observed association with better systemic hemodynamic stability. Thirdly, it is well known that polytrauma patients present a state of severe endothelial injury, coagulation derangements, and systemic inflammation [ 37 ]. In this clinical context, some evidence supported the idea that citrate, in comparison with heparin, could improve the biocompatibility of the extracorporeal circuit, limiting the interaction between the filter membrane and the blood components [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with post-traumatic bleeding can develop hemorrhagic shock due to blood volume depletion and subsequent reduction in oxygen delivery to the microvessels and microcirculation, leading to a state of metabolic acidosis [22]. Isolated and transient hemorrhagic shock may be tolerated [23]. Hypocoagulopathy derived from the replacement of blood loss with large volumes of fluids and blood supports that lead to dilution of proteins and enzymes required for the formation of clots [24].…”
Section: Physiopathology Of Coagulopathy and Bleeding In Traumamentioning
confidence: 99%